(untitled) (Western European Journal of Historical Events and Social Science, 2024)
In the following article the valuable information on the issues of history of economy of the late period of the emirate of Bukhara in the end of the 19th century and the beginning of the 20th century, including the crisis in the karakul sheepskin is presented. Several aspects of crisis in karakul sheepskin trade are analysed